Contribution and Condition of the Agricultural Sector to Gross Regional Domestic Product in Mojokerto Regency - Gilbert Wong; Syarif Imam Hidayat; Dona Wahyuning Laily (Universitas Muhammadiyah Palembang, 2025)
Mojokerto Regency is known as a major producer of rice, soybeans, and corn. Rice, as the main commodity, shows relatively stable production with seasonal fluctuations influenced by planting patterns and weather conditions. Corn and soybeans have experienced significant production increases, driven by rising market demand and government programs promoting food crop diversification. This study aims to analyze the contribution, trend, and growth of the agricultural sector to the Gross Regional Domestic Product (GRDP) in Mojokerto Regency. The methods used include Contribution Analysis, Trend Analysis, and Shift Share Analysis, based on time series data from 2014 to 2023. The results show that the agricultural sector makes a significant contribution to the GRDP of Mojokerto Regency, although it remains below the manufacturing sector. Trend analysis indicates a tendency for the agricultural sector’s contribution to increase throughout the study period. Meanwhile, the Shift Share results reveal that the agricultural sector has competitive advantages and a positive regional growth effect compared to the average performance of the agricultural sector in East Java Province. The study concludes that the agricultural sector continues to play a strategic role in the regional economy and should be supported by sustainable development policies to optimize its contribution.